2020
DOI: 10.1186/s13690-020-00457-4
|View full text |Cite|
|
Sign up to set email alerts
|

Decomposing socioeconomic inequality in dental caries in Iran: cross-sectional results from the PERSIAN cohort study

Abstract: Background: The current study aimed to measure and decompose socioeconomic-related inequalities in DMFT (decayed, missing, and filled teeth) index among adults in Iran. Methods: The study data were extracted from the adult component of Prospective Epidemiological Research Studies in IrAN (PERSIAN) from 17 centers in 14 different provinces of Iran. DMFT score was used as a measure of dental caries among adults in Iran. The concentration curve and relative concentration index (RC) was used to quantify and decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
1
16
0
3
Order By: Relevance
“…Other studies in Iran on the individuals’ behavioural compliance with dental prevention practice and utilization from dental services showed similar results in line with our study findings 25,38‐40 . However, another study showed a pro‐poor inequality in dental caries that is highly associated with poor dental self‐care 41,42 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other studies in Iran on the individuals’ behavioural compliance with dental prevention practice and utilization from dental services showed similar results in line with our study findings 25,38‐40 . However, another study showed a pro‐poor inequality in dental caries that is highly associated with poor dental self‐care 41,42 …”
Section: Discussionsupporting
confidence: 92%
“…25,[38][39][40] However, another study showed a pro-poor inequality in dental caries that is highly associated with poor dental self-care. 41,42 As our previous expectation, the most influential factor in explaining the inequality of the DSS was SES. Decomposition of the inequality contributors showed there was a pro-rich gradient in the use of toothbrush, toothpaste and dental floss.…”
Section: Discussionmentioning
confidence: 61%
“…Oral health is an important part of public health, in that, it has a major impact on the quality of life, well-being and the overall health of children [1,2]. A healthy mouth enables a person to eat, talk, communicate better, and socialize [3].…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error of the ethical code in the Ethics approval and consent to participate section.…”
mentioning
confidence: 99%
“…Correction to: Archives of Public Health 78, 75 (2020) https://doi.org/10.1186/s13690-020-00457-4 Following publication of the original article [1], the authors reported an error of the ethical code in the Ethics approval and consent to participate section.…”
mentioning
confidence: 99%